Determinants of bilateral current account balance between the Eurozone and the United States - Gerassimos Bertsatos (European Journal of Government and Economics (EJGE), 2022)
Long- and short-run current account balance (CAB) determinants of the nineteen Eurozone (EZ) member states vis-a-vis the United States (US) are examined. Particularly, the competitiveness of the EZ vs the US, the relationship between the current account deficit and the budget deficit (twin deficit), and other factors determining the current account balance are studied. Quarterly data was used in a sample of the nineteen EZ member states with the US as a trading partner over the period 2008 - 2018. It is found that the CAB in the long run has a positive relationship with the real interest rate, real exchange rate, Gross Domestic Product (GDP) per capita, and exchange rate volatility, but a negative relationship with the fiscal balance. In the short run, it is notable that only the real exchange rate affects the current account balance. Finally, policy implications are discussed regarding the determinants of the current account.
Keywords: F30; F32; F40; F41; 330; current account determinants; economic policy; PMG method; Eurozone; USA